2016
DOI: 10.6113/jpe.2016.16.4.1565
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis and Improvement of the Capacitor Current Active Damping of the LCL Filters in Grid-Connected Applications

Abstract: For grid-connected LCL-filtered inverters, dual-loop current control with an inner-loop active damping (AD) based on capacitor current feedback is generally used for the sake of current quality. However, existing studies on capacitor current feedback AD with a control delay do not reveal the mathematical relation among the dual-loop stability, capacitor current feedback factor, delay time and LCL parameters. The robustness was not investigated through mathematical derivations. Thus, this paper aims to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
(80 reference statements)
0
14
0
Order By: Relevance
“…For instance, with one-sample delay (i.e., T d = T s ), the resonance still exists if a is between 1/6 and 1/2, as also analyzed in [26][27][28][29][30][31][32]34]. If (10) is fulfilled, the feedback AD in Fig.…”
Section: Digital Control Delay Impactmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, with one-sample delay (i.e., T d = T s ), the resonance still exists if a is between 1/6 and 1/2, as also analyzed in [26][27][28][29][30][31][32]34]. If (10) is fulfilled, the feedback AD in Fig.…”
Section: Digital Control Delay Impactmentioning
confidence: 99%
“…Besides delay, in practical application the filter parameters may vary from their design values and the grid at the PCC has non-negligible impedance. The studies in [6,[27][28][29][30][31][32], and [64][65][66][67][68] showed that the resonance frequency is significantly reduced when the filter parameters and the grid impedance are varied.…”
Section: Stability and Robustness Improvementmentioning
confidence: 99%
See 3 more Smart Citations